DIGITAL MARKETING OF FISHERY PRODUCTS, MARKETING STRATEGY DURING THE COVID-19 PANDEMIC - Nurhuda Annaastasia; Desi Sriwulan; Wa Jali; Abdul Sarifin (Jurusan Perikanan dan Kelautan, 2022)
The development of technology affects people's lifestyles, especially in meeting their daily needs. This is what underlies business actors starting to look at digital marketing marketing. This study aims to determine the marketing strategy of processed fishery products using digital marketing during the Covid-19 pandemic. This research was conducted from June to September 2021 in Kendari City. The results of the study show that there is a relationship between the application of digital marketing with sales volume and marketing strategies by utilizing more than one digital by providing an attractive appearance for consumers.